Correction: Martin et al. ApeTI: A Thermal Image Dataset for Face and Nose Segmentation with Apes. Signals 2024, 5, 147–164 - Pierre-Etienne Martin; Gregor Kachel; Nicolas Wieg; Johanna Eckert; Daniel B. M. Haun (Signals)
Addition of Authors [...]